Kinetics of Austenite Layer Growth on the Surface of Fe-23Cr-2.4Mo Ferritic Stainless Steel During Solution Nitriding - Kh. Farjam Hajiagha (Journal of Advanced Materials in Engineering, 2017)
In this study, the kinetics of austenite layer growth on the surface of Fe-23Cr-2.4Mo ferritic stainless steel during solution nitriding and the effects of nitrogen adding on microstructure and hardness of the steel have been investigated. Steel plates of 2 mm thick were solution-nitrided at 1200˚C under nitrogen pressure of 0.25 MPa for 2, 3, 6, 9, 12 hours. Microstructure, the thickness of austenite layer and the hardnes of the nitrided samples, were investigated by using optical microscope, X-ray Diffraction (XRD) and microhardness measurements. The results showed that during solution nitriding, nitrogen diffuses through the lattice and grain boundaries and transforms ferrite to austenite phase, with average nitrogen diffusion coefficient of 6.54×10-5 mm2s-1. The thickness of the austenite layer formed on the samples surfaces increased proportional to the square root of the nitriding time, so that after 12 hours niriding, the whole thickness of the ferritic sample with hardness of 262 HV0.1 transformed to austenite with hardness of 420 HV0.1.